Second Five Year Plan District Plan Bombay State Sorath District - Planning Commission (Planning Commission)
The present Sorath district came into existence in the year 1949 on amalgamation of a number of small princely states, chief among them being Junagadh, Manavadar, Mangrol, Bantwa, Sardargadh, Sultanabad, Porbandar, and Bilkha. Prior to re-organisation of the States, this district formed part of the former Saurashtra State and it now forms part of the Rajkot region of the reorganised Bombay State. LOCATION and TOPOGRAPHY The Sorath district lies between 20.44° N and 24-40° N lattitude and between 69-40° E and 71-50° E longitude.
Bombay State